Globalization and health : a framework for analysis and action - Woodward, David (2001)
Presents a conceptual framework for the linkages between economic globalization and health, with the intention that it will serve as a basis for synthesizing existing relevant literature identifying gaps in knowledge, and ultimately developing national and international policies more favourable to health. Proposes a programme of action to optimize the health effects of economic globalization.